Penyintas di Lumpur Tanpa Batas: Potret Pemulihan Sosial Ekonomi Masyarakat Terdampak Bencana Lumpur Lapindo - Miftakhul Iftita; Siti Zurinani (Endogami: Jurnal Ilmiah Kajian Antropologi, 2018)
THIS -- paper discusses about the socio-economic recovery efforts of communities affected by the Lapindo mud disaster in Kedungsolo, the relocation Village. The data of this paper is taken by using ethnography method, which resulted in the conclusion of the post-disaster socio-economic recovery efforts by the Renokenongo community since the evacuation of Pasar Baru Porong. The Renokenongo community formed the Paguyuban Warga Renokenongo Menolak Kontrak (Pagar Rekontrak) as the beginning of the socio-economic recovery effort communally. While personally, every household also makes different recovery efforts depending on how they access existing recovery resources. This recovery effort also received support from several related parties, both government agencies and private institutions.